2009
DOI: 10.2746/042516409x475337
|View full text |Cite
|
Sign up to set email alerts
|

A rapid molecular method for diagnosing epidemic dermatophytosis in a racehorse facility

Abstract: This study demonstrates that the PCR-based molecular diagnostic method is sensitive and specific and offers fast precise diagnosis of dermatophytosis in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Microsporum equinum , rather than M. canis , may prove to be the second most common factor of equine ringworm in North America. Among racehorse herds from the Korean Racehorse Authority, 38 racehorses were definitively diagnosed with dermatophytosis and T. mentagrophytes was the prevalent infectious agent . A previous study reported that T. verrucosum was the most prevalent dermatophyte in horses in Egypt .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Microsporum equinum , rather than M. canis , may prove to be the second most common factor of equine ringworm in North America. Among racehorse herds from the Korean Racehorse Authority, 38 racehorses were definitively diagnosed with dermatophytosis and T. mentagrophytes was the prevalent infectious agent . A previous study reported that T. verrucosum was the most prevalent dermatophyte in horses in Egypt .…”
Section: Discussionmentioning
confidence: 99%
“…Dermatophytosis is considered one of the most important fungal skin diseases which infects animals and is transmitted from animal to animal, from animal to human and from human to animals . Dermatophytes are filamentous fungi, which invade keratinized tissues of humans and animals, causing mild to severe, localized and/or diffuse infections .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCR assay was performed with the DNA Thermo Cycler ( TC‐512 ). Primers used in our study were those reported by Chung and others (2010), CHS1 1S (5′‐ CAT CGA GTA CAT GTG CTC GC) and CHS1 1R (5′‐CTC GAG GTC AAA AGC ACG CC), which amplify a 450‐bp fragment within the CHS1 gene. The reactions were performed in a final volume of 25 μL containing 3 μL of template DNA, 2·5 μL of reaction buffer, 0·4 mM of deoxynucleoside triphosphates (dNTPs), 1·5 mM of MgCl 2 , 0·3 μL of Taq DNA polymerase and 0·4 mM of each primer.…”
Section: Methodsmentioning
confidence: 99%